Artificial intelligence-powered image recognition retail checkout systems - Malyssa Alias; Dhaifina Saidi; Lim Jia Huey; Lee Qing Fang; Durghaashini S. Ragunathan; JosephNg Poh Soon; Phan Koo Yuen; Lim Jit Theam; Wong See Wan (International Journal of Advances in Applied Sciences, 2026)
The integration of artificial intelligence (AI) with big data analytics leads to substantial transformations in the retail sector. This research explores the impact of AI-powered image recognition checkout systems on the retail industry, focusing on operational efficiency, customer experience, and resource waste. Employing a mixed-methods approach, this study combines usability testing and data analytics to assess the viability of this technology in attaining automation and accuracy in retail operations. The study focuses on the creation of robust, resource-efficient systems that foster long-term industrial growth. The findings show that AI-powered solutions not only speed the checkout process but also contribute to sustainable infrastructure by reducing resource consumption and increasing energy efficiency. This report offers significant information, like the impact of AI-powered image recognition checkout systems on operational efficiency, customer experience, and the role of AI in promoting sustainable infrastructure for retailers and governments looking to advance the digitalization of the retail industry.